Emergency peripartum hysterectomy- a study in tertiary care centre and medical college in Hubli, North Karnataka, India - Kittur, Sahaja; D., Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Post-partum haemorrhage is a significant cause of maternal mortality and morbidity. The objective of the study was to evaluate the incidence, predisposing factors & associated complications and outcome of emergency peripartum hysterectomy. Methods: It is a prospective analysis of emergency peripartum hysterectomy conducted at tertiary care centre at Karnataka Institute of Medical Sciences, Hubli, Karnataka, India between June 2013 to December 2015. Age, parity, traumatic or atonic PPH, risk factors, complications were all studied in detail and analysed. Results: 43 women underwent peripartum hysterectomy among 28,620 deliveries, accounting to an incidence of 0.15%. Incidence of subtotal hysterectomy after caesarean delivery was higher as compared to vaginal deliveries. The common indications were uterine atony (46.5%), uterine rupture of scared and unscared uterus (44.1%), placenta previa of major degree and sepsis (6.9%). Post-operatively 13 patients developed DIC (30.2%), 5 patients developed febrile illness (11.6%), 5 patients of ruptured uterus experienced injury to the bladder (11.6%). Maternal mortality in this study was 13.9%. Conclusions: Hysterectomy is a lifesaving procedure to control postpartum hemorrhage, but is associated with significant maternal morbidity and mortality. Uterine atony, uterine ruptures, also due to prior caesarean delivery, placenta previa were identified as risk factors. The incidence in this part of Karnataka was found to be significantly high due to referral cases from neighboring 5 government district hospitals. Hence only proper awareness, timely referral and correction of anemia are the key factors to be addressed to this part of the state.